Association of Cardiovascular Autonomic Neuropathy and Distal Symmetric Polyneuropathy with All-Cause Mortality: A Retrospective Cohort Study - Orsolya E. Vági; Márk M. Svébis; Beatrix A. Domján; Anna E. Körei; Ildikó Istenes; Zsuzsanna Putz; Szilvia Mészáros; Noémi Hajdú; Magdolna Békeffy; Solomon Tesfaye; Péter Kempler; Viktor J. Horváth; et al. (Journal of Diabetes Research)
Background. People with diabetic cardiovascular autonomic neuropathy (CAN) have increased cardiovascular mortality. However, the association between distal symmetric polyneuropathy (DSPN) or CAN with all-cause mortality is much less investigated. Thus, we set out to examine the effect of CAN and DSPN on all-cause mortality in a well-phenotyped cohort. Methods. All diabetes cases (n=1,347) from the catchment area of a secondary diabetes care centre who had medical examination including neuropathy assessment between 1997 and 2016 were followed up for all-cause mortality in the NHS Hungary reimbursement database until 2018. We investigated the association of CAN (Ewing tests) and DSPN (Neurometer) with all-cause mortality using Cox models stratified by diabetes type. Results. Altogether, n=131/1,011 persons with type 1/type 2 diabetes were included. Of the participants, 53%/43% were male, mean age was 46±12/64±10 years, diabetes duration was 13±10/7±8 years, 42%/29% had CAN, and 39%/37% had DSPN. During the 9±5/8±5-year follow-up, n=28/494 participants died. In fully adjusted models, participants with type 1 diabetes patients with versus without DSPN had an increased mortality (HR 2.99, 95% CI 1.4-8.63), while no association with CAN was observed. In type 2 diabetes, both DSPN and CAN independently increased mortality (HR 1.32, 95% CI: 1.07-1.64, and HR 1.44, 95% CI: 1.17-1.76). Conclusions. Our results are compatible with an increased risk of mortality in people with type 1 diabetes and DSPN. Furthermore, we report a similarly strong association between DSPN and CAN and all-cause mortality in type 2 diabetes mellitus.